2011
DOI: 10.1007/s11089-011-0346-7
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, Secondary Traumatic Stress, and Social Support

Abstract: The current study examines the extent to which selected work-related variables differentially predict burnout and secondary traumatic stress (STS) and the degree to which social support mitigates both of these occupational stress syndromes. Multiple regression performed on responses from 331 professional chaplains found that:(1) the number of years worked in the same employment position was positively associated with burnout but not STS; (2) STS, but not burnout, was positively associated with the number of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
61
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 55 publications
12
61
1
4
Order By: Relevance
“…Research advanced by Galek, Flannelly, Greene, and Kudler (2011) found the following key predictors in the occurrence of secondary trauma syndrome (STS) and burnout:…”
Section: Definitions Of Stress Related Prevention Strategies and Promentioning
confidence: 99%
“…Research advanced by Galek, Flannelly, Greene, and Kudler (2011) found the following key predictors in the occurrence of secondary trauma syndrome (STS) and burnout:…”
Section: Definitions Of Stress Related Prevention Strategies and Promentioning
confidence: 99%
“…Moreover, independent and moderating variables were centred on their respective means to reduce multicollinearity between main effects and interactional terms, and to increase the interpretability of the weights for the interaction terms (Cohen, Cohen, West, & Aiken, 2013). In addition, gender, age, and severity of trauma were considered as compounding variables and controlled in each analysis, due to the relations between gender, age, and trauma severity and burnout (Galek, Flannelly, Greene, & Kudler, 2011; Lee, Puig, Lea, & Lee, 2013; Salmela-Aro & Tynkkynen, 2012). Specifically, we inserted compounding variables (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Ainsi, la nature même du travail en relation d'aide constitue l'élément initial, mais aussi un facteur de risque pour la FC et le TV. En ce sens, plus un intervenant passe du temps avec des clients souffrants et victimes de traumatismes, plus le risque de développer du stress traumatique secondaire augmente, favorisant ainsi la FC et le TV (Baird & Kracen, 2006;Brady et al, 1999;Bober & Regehr, 2006;Brady et al, 1999;Bell et al, 2003;Craig & Sprang, 2009;Cunningham, 2003;Figley, 2002b;Galek et al, 2011;Pearlman & Mac Ian, 1995;Perreault, 2004, Shalvi et al, 2011Sprang, Clark & Whitt-Woosley, 2007;VanDeusen & Way, 2006). …”
Section: La Nature Et La Charge De Travailunclassified
“…En plus de la présence d'un réseau social permettant au travailleur d'éviter ou de briser l'isolement social, l'accès à une forme de soutien affectif ou instrumental par les gens de son entourage s'ajoute aux facteurs d'influence positive (Brady et al, 1999;Collins & Long, 2003b;Conrad & Kellar-Guenther, 2006;Dunkley & Whelan, 2006a, b;Figley, 2002b;Figley & Barnes, 2005;Galek, Flannelly, Greene & Kudler, 2011;Harrison & Westwood, 2009;Killian, 2008;Newell & MacNeil, 2010;Phipps & Byrne, 2003;Shauben & Frazier, 1995;Stamm, 1998;Tehrani, 2010).…”
Section: 4jj Le Mode De Vie Et Le Réseau Socialunclassified
See 1 more Smart Citation